Mesoporous MPC@TMG, a basic heterogeneous organocatalyst in C–C/C–N bond forming reactions: Tandem multicomponent synthesis of 5-amino-pyrazole-4-carbonitriles and 1H-pyrazolo [1,2-b] phthalazine-5, 10-dione derivatives under sustainable reaction conditions - Atif Mustafa; Nazia Zameer; Nida Khan; Zeba N. Siddiqui (Tetrahedron Green Chem)
A metal-free, effective, and sustainable protocol has been developed to carry out C–N and C–C bond-forming reactions leading to the formation of 5-amino-pyrazole-4-carbonitriles and 1H-pyrazolo [1,2-b] phthalazine-5, 10-dione derivatives via a tandem multicomponent reaction using mesoporous MPC@TMG as a basic heterogeneous organocatalyst. The reactions were performed in aqueous medium at room temperature. The synthesized organocatalyst MPC@TMG was characterized by numerous spectroscopic techniques such as Fourier Transform Infrared (FTIR), Powder X-ray diffraction (PXRD), Brunauer-Emmett-Teller (BET), Scanning Electron Microscope (SEM), Energy Dispersive X-ray (EDX), elemental mapping, and Thermal Gravimetric (TG) analyses. MPC@TMG displayed excellent catalytic potential, high thermochemical stability, and reusability for up to eight catalytic runs and offered the title compounds in excellent yields (>90 %) in a short reaction time (6–15 min). The synthesized compounds were characterized through FTIR, 1H, and 13C Nuclear Magnetic Resonance (NMR) spectroscopy. The use of water as a green solvent, the generality of the method, easy catalyst recovery, a simple work-up procedure, and zero involvement of any metal are the key features of the present protocol making it green and sustainable for the synthesis of the desired heterocycles and is supported by the calculations for green metrics parameters.